(3Gdaf GdeUQi GdMOjK(B- (3eOGQSg h CSGdjHgG(B/ s ((3GdbGgQI;s (3GdeLdS GdCYdi ddKbGaI; s, 2009)
Title translation: Contemporary Egyptian Art- Its schools and practices. By Zuha Ahmed.
Arabic
Keywords: Contemporary art; N5300-7418 Visual Arts- History; Egypt